Management and outcome of patients with acute ischemic stroke and tandem carotid occlusion in the ESCAPE-NA1 trial. (4th May 2021) - Marko, Martha; Cimflova, Petra; Poppe, Alexandre Y; Kashani, Nima; Singh, Nishita; Ospel, Johanna; Mayank, Arnuv; van Adel, Brian; McTaggart, Ryan A; Nogueira, Raul G; Demchuk, Andrew M; Rempel, Jeremy L; et al.
Abstract : Background: The optimal treatment and prognosis for stroke patients with tandem cervical carotid occlusion are unclear. We analyzed outcomes and treatment strategies of tandem occlusion patients in the ESCAPE-NA1 trial. Methods: ESCAPE-NA1 was a multicenter international randomized trial of nerinetide versus placebo in 1105 patients with acute ischemic stroke who underwent endovascular treatment. We defined tandem occlusions as complete occlusion of the cervical internal carotid artery (ICA) on catheter angiography, in addition to a proximal ipsilateral intracranial large vessel occlusion. Baseline characteristics and outcome parameters were compared between patients with tandem occlusions versus those without, and between patients with tandem occlusion who underwent ICA stenting versus those who did not. The influence of tandem occlusions on functional outcome was analyzed using multivariable regression modeling. Results: Among 115/1105 patients (10.4%) with tandem occlusions, 62 (53.9%) received stenting for the cervical ICA occlusion. Of these, 46 (74.2%) were stented after and 16 (25.8%) before the intracranial thrombectomy. A modified Rankin Score (mRS) of 0–2 at 90 days was achieved in 82/115 patients (71.3%) with tandem occlusions compared with 579/981 (59.5%) patients without tandem occlusions. Tandem occlusion did not impact functional outcome in the adjusted analysis (OR 1.5, 95% CI 0.95 to 2.4). Among the subgroup of patients with tandem occlusion, cervical carotid stenting was not associated with different outcomes compared with no stenting (mRS 0–2: 75.8% vs 66.0%, adjusted OR 2.0, 95% CI 0.8 to 5.1). Conclusions: Tandem cervical carotid occlusion in patients with acute large vessel stroke did not lower the odds of good functional outcome in our study. Functional outcomes were similar irrespective of the management of the cervical ICA occlusion (stenting vs not stenting).